FINGER PRINT BIKE STARTER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This fingerprint system is a project to prevent motorcycle thefts these days. So with our project or initiative, this will reduce the risk of thefts that happen in India. We got this idea based on the collected problem statement which is nowadays motorcycle are easily being stolen by the thieves. The objective of this project is to upgrade the safety system, to ease the ignition of the bike and reduce the loss of motorcycles in the present time. Basically, we are making a new way to start a bike that is originally used starter. By using our project, they can ignite their motorcycle just by using their fingerprint. In our preliminary study, this project requires us to study about electronic devices and circuits. Thus, we have to make research to make a circuit so, the fingerprint sensor will work well. In conclusion, we hope our project could decrease the rate of stolen motorcycle and give a new interesting way of starting your motorcycle.